Osteoarthrosis: An old disease, novel approaches - Aleksandr Ivanovich Dubikov (Современная ревматология, 2013)
Osteoarthrosis (OA) is one of the most common diseases in the elderly; nonetheless, its treatment calls for further investigation. Present views are changing on the pathophysiology of OA, the role of the subchondral bone (SB), and an interaction between SB and articular cartilage in the natural history of the disease. Recent data point to novel therapeutic strategies, one of which is to use strontium ranelate in order to delay the progression of chondrolysis in knee and hip OA.